Accounting for cryptocurrencies under FASB and the financial reporting impact on large US corporations in 2020 and beyond. (11th April 2023) - Currie, Hailey; Boyer-Davis, Stacy; Oswald, Raina
Cryptocurrencies are a highly debated subject in the US framework. The issues discussed will be accounting for cryptocurrencies in the USA and with a concentration on corporations. These problems involve government entities, market volatility, accounting methods, financial statement implications, public opinions, initial coin offers (ICOs), among others. Specifically, the topic of how to classify cryptocurrencies is discussed and the urge for decision-makers to make changes. Many opinions on the best way to classify cryptocurrencies exist. However, no official guidance concerning cryptocurrencies has been established. Cryptocurrencies are currently being treated in different ways in the accounting, financial, and tax worlds, which needs to be confronted. Additionally, the topic of cryptocurrency transactions' impact on financial statements, the valuation of cryptocurrencies, and the taxation of cryptocurrencies are evaluated. Furthermore, the topics of how different accounting and tax treatments of cryptocurrencies will impact the financial statements if the rules were to change.